A Simple, Highly Efficient Method for Heterologous Expression in Mammalian Primary Neurons Using Cationic Lipid-mediated mRNA Transfection - Williams, Damian J.; Puhl, Henry L.; Ikeda, Stephen R. (Frontiers in Neuroscience, 2010)
Expression of heterologous proteins in adult mammalian neurons is a valuable technique for the study of neuronal function. The postmitotic nature of mature neurons prevents effective DNA transfection using simple, cationic lipid-based methods. Adequate heterologous protein expression is often only achievable using complex techniques that, in many cases, are associated with substantial toxicity. Here, a simple method for high efficiency transfection of mammalian primary neurons using in vitro-transcribed mRNA and the cationic lipid transfection reagent Lipofectamine 2000 is described. Optimal transfection conditions were established in adult mouse dissociated dorsal root ganglion (DRG) neurons using a 96-well based luciferase activity assay. Using these conditions, a transfection efficiency of 25% was achieved in DRG neurons transfected with EGFP mRNA. High transfection efficiencies were also obtained in dissociated rat superior cervical ganglion (SCG) neurons and mouse cortical and hippocampal cultures. Endogenous Ca2+ currents in EGFP mRNA-transfected SCG neurons were not significantly different from untransfected neurons, which suggested that this technique is well suited for heterologous expression in patch clamp recording experiments. Functional expression of a cannabinoid receptor (CB1R), a G protein inwardly-rectifying K+ channel (GIRK4) and a dominant-negative G protein α-subunit mutant (GoA G203T) indicate that the levels of heterologous protein expression attainable using mRNA transfection are suitable for most functional protein studies. This study demonstrates that mRNA transfection is a straightforward and effective method for heterologous expression in neurons and is likely to have many applications in neuroscience research.